What Are the Post-Operative Complication Rates and Quality of Life Improvements Following Tonsillectomy in Children With Chronic Tonsillitis? : a Systematic Review - Azhari, Fierda Ovita; Syukrinto, Gustav (Syntax Corporation Indonesia, 2025)
Chronic tonsillitis is a significant health issue in children, characterized by recurrent throat infections that diminish their quality of life. Tonsillectomy is a common surgical solution, but a comprehensive analysis balancing its benefits against post-operative risks is needed. The purpose of this study was to evaluates post-operative complication rates and quality of life improvements following tonsillectomy in children with chronic tonsillitis. This review followed PRISMA 2020 guidelines. A systematic search was conducted across PubMed, Semantic Scholar, Springer, Google Scholar, and Wiley Online Library for studies published in the last decade. Eleven studies were included. The findings consistently showed significant improvements in quality of life post-tonsillectomy, as measured by validated instruments like the Pediatric Throat Disorders Outcome Test (T-14) and the Pediatric Quality of Life Inventory (PedsQL-P). Post-operative complication reporting was heterogeneous. The most frequently quantified complication was post-tonsillectomy hemorrhage, with rates varying from 2.7% to 7.9% depending on the surgical technique. Other reported complications included pain, halitosis, and uvula edema. Long-term follow-up (5 years) in two studies showed sustained quality of life benefits.